Efeito do teor de umidade sobre o pré-tratamento a vapor e a hidrólise enzimática do bagaço de cana-de-açúcar - Ana Paula Pitarelo; Thiago Alessandre da Silva; Patricio Guillermo Peralta-Zamora; Luiz Pereira Ramos (Química Nova, 2012)
The effect of moisture content in the steam treatment and enzymatic hydrolysis of sugarcane bagasse was evaluated. Steam treatment was perfomed at 195-210 ºC for 4-8 min using cane bagasse with moisture contents in the range 16-100 wt% (dry basis). Increased moisture contents not only had a positive influence in recovery of main cane biomass components but also resulted in better substrates for enzymatic hydrolysis. As a result, drying is not required for optimal pretreatment and enzymatic hydrolysis of sugarcane bagasse, which can be processed into second generation ethanol immediately after crushing and hot water washing.